A Parietal Biomarker for ADHD Liability: As Predicted by the Distributed Effects Perspective Model of ADHD - Hale, T. Sigi; Wiley, Joshua F.; Smalley, Susan L.; Tung, Kelly L.; Kaminsky, Olivia; McGough, James J.; Jaini, Ashwin M.; Loo, Sandra K. (Frontiers in Psychiatry, 2015)
Background: We previously hypothesized that poor task-directed sensory information processing should be indexed by increased weighting of right hemisphere (RH) biased attention and visuo-perceptual brain functions during task operations, and have demonstrated this phenotype in ADHD across multiple studies, using multiple methodologies. However, in our recent Distributed Effects Model of ADHD, we surmised that this phenotype is not ADHD specific, but rather more broadly reflective of any circumstance that disrupts the induction and maintenance of an emergent task-directed neural architecture. Under this view, increased weighting of RH biased attention and visuo-perceptual brain functions is expected to generally index neurocognitive sets that are not optimized for task-directed thought and action, and when durable expressed, liability for ADHD. Method: The current study tested this view by examining whether previously identified rightward parietal EEG asymmetry in ADHD was associated with common ADHD characteristics and comorbidities (i.e., ADHD risk factors). Results: Barring one exception (non-right handedness), we found that it was. Rightward parietal asymmetry was associated with carrying the DRD4-7R risk allele, being male, having mood disorder, and having anxiety disorder. However, differences in the specific expression of rightward parietal asymmetry were observed, which are discussed in relation to possible unique mechanisms underlying ADHD liability in different ADHD RFs. Conclusion: Rightward parietal asymmetry appears to be a durable feature of ADHD liability, as predicted by the Distributed Effects Perspective Model of ADHD. Moreover, variability in the expression of this phenotype may shed light on different sources of ADHD liability.